2010
DOI: 10.1111/j.1399-0012.2010.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteric conversion after pancreatic transplantation: resolution of symptoms and long‐term results

Abstract: For the treatment of symptoms associated with BD, EC results in excellent long-term graft function and significant resolution of symptoms even years after SPK. Postoperative morbidity after EC including early reoperation and graft loss, however, has to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Enteric conversion frequency ranged from 10% to 40% (Table 3) [79 -86] . Several authors reported that enteric conversion resulted in superb long-term graft function coupled with marked symptom improvement even when performed several years following SPK transplant [84,87,88] . Despite urological morbidity and the finite risk of enteric conversion, 5-year actuarial patient and graft survival rates with bladder drainage were excellent and most complications could be managed with conservative (nonoperative) therapy.…”
Section: El-hennawy H Et Al Exocrine Drainage In Pancreas Transplantsmentioning
confidence: 99%
“…Enteric conversion frequency ranged from 10% to 40% (Table 3) [79 -86] . Several authors reported that enteric conversion resulted in superb long-term graft function coupled with marked symptom improvement even when performed several years following SPK transplant [84,87,88] . Despite urological morbidity and the finite risk of enteric conversion, 5-year actuarial patient and graft survival rates with bladder drainage were excellent and most complications could be managed with conservative (nonoperative) therapy.…”
Section: El-hennawy H Et Al Exocrine Drainage In Pancreas Transplantsmentioning
confidence: 99%
“…There are also favorable results for the conversion of bladder to enteric drainage without increased risk of graft loss [26]. However, when enteric conversion was performed in an emergent situation due to anastomosis leakage, the results could be worse than in the elective cases [1]. In our series, only the patient who underwent enteric conversion with duodenal leakage had recurrent duodenal leaks and peritonitis.…”
Section: Discussionmentioning
confidence: 80%
“…Simultaneous pancreas-kidney (SPK) transplantation is an established therapeutic approach for patients with insulin-dependent diabetes mellitus and end-stage renal disease [1]. Improvement of quality of life and potential reductions in macrovascular and microvascular complications have been documented in many publications [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…При не-возможности адекватной коррекции возможно вы-полнение отсроченной конверсии анастомоза с фор-мированием дуоденоэнтероанастомоза [27,64,68].…”
Section: хирургические аспекты трансплантации поджелудочной железы меunclassified